(Re)-reforming external quality assurance in higher education – the Finnish case. Issue 4 (1st October 2020) - Overberg, Jasmin; Lehmkuhl, Pia; Schütz, Marcel; Röbken, Heinke
ABSTRACT: In this article, we analyse reforms of academic quality assurance in light of organizational theory using the case example of Finnish higher education. Our purpose is to shed light on the processes behind repeated reforms and the motivation to continuously modify quality models that have only been in use for a relatively short period of time. In our discussion, we propose interpreting the continuous change and strong differentiation of quality management in a positive light. The development, alteration, and promotion of quality management can be considered an attempt at continuous self-improvement; they also significantly contribute to (reform-driven) communication about quality. The changes also serve a number of other functions, which we discuss in the final section of our paper.